P-133 Combined oncology & palliative care clinics; hospice in-patient stays and place of death. (1st March 2017) - Broadbent, Anna; Mader, Amman; Benham, Beccy; Palmer, Joanne; Campbell, Carolyn; Newman, Rachel; Stevens, Deborah; Gibbins, Jane
Abstract : Background: Early Specialist Palliative Care (SPC) introduced to patients with advanced lung cancer has been proven to enhance quality-of-life and improve survival. Combined Oncology and Palliative Care Clinics (COPCC) at Royal Cornwall Hospital Trust enable patients to be reviewed by palliative care consultants whilst attending for oncology review; facilitating the two specialities to run in parallel to improve patient care. The aims of this project were to explore the use of inpatient hospice facilities of all patients, and place of death those for those patients who died. Methods: Retrospective case-note review of 150 consecutive patients between 01/2016-06/2016. Data collected by three medical students. Results: Admissions to hospice: 18/150 patients (12%) had at least one hospice admission, with the most common primary reason for admission being symptom control (83%). Total number of admissions of any one patient ranged from one to seven. Length of stay range; one to 46 days, with a median value of nine days. Patients were known to the hospice up to 65 months prior to death. 11/18 patients died during their last hospice admission, and seven were discharged home. Place of death: 29/150 (19%) patients died at the time of data collection; 12 (41%) died at home, 11 (38%) died in a hospice, 3 (10.5%) died in acute 3 (10.5%) or 3 (10.5%) community hospitals. Conclusion: Access to SPC in COPCCs appears to enable early contact with inpatient hospice units, and enable more patients to die in hospices and at home. 38% of this study's deceased patients died in a hospice; a 2.3 fold increase compared to hospice deaths of cancer patients specifically (16.4%).2 The number of deaths is small and warrants follow-up studies. References: . Temel JS, et al . Early palliative care for patients with metastatic non-small-cell lung cancer. NEJM 2010;19:733–42 . National End of Life Care Intelligence Network.